2010
DOI: 10.5137/1019-5149.jtn.2914-10.0
|View full text |Cite
|
Sign up to set email alerts
|

Anterior tarsal tunnel syndrome secondary to missed talus fracture: a case report

Abstract: The anterior tarsal tunnel syndrome (ATTS) has first been described by Kopell and Thompson in 1963. The anterior tarsal tunnel is formed by the fascia lining the inferior extensor retinaculum and talus as well as the navicular bone. Many ATTS cases with various etiologies have been reported since the first description. We report here an ATSS case resulting from a fibro-osseous structure that occurred after a missed talus fracture. The ATTS diagnosis can be made with a comprehensive clinical neurological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In ballet dancers, stretching of the nerve due to extreme planter flexion was described by Borges ( 7 ). Cetinkal et al reported such a case in a missed talar fracture ( 8 ). Akyuz after evaluating 325 symptomatic feet found only 14 (4.3%) patients who had ATTS ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In ballet dancers, stretching of the nerve due to extreme planter flexion was described by Borges ( 7 ). Cetinkal et al reported such a case in a missed talar fracture ( 8 ). Akyuz after evaluating 325 symptomatic feet found only 14 (4.3%) patients who had ATTS ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 Also, Cetinkal et al reported that fibro-osseous structure occurred after a missed talus fracture could cause ATTS. 8 Moreover, Gani et al reported such a case with the thrombosed dorsalis pedis artery. 9 Patients may describe hyperesthesia and/or paresthesia between the first and second finger and pain at the back of foot.…”
mentioning
confidence: 99%
“…11 On the other hand, it is known that most normal cases reveal fibrillation in EDB because of local trauma so it may be neglected. 8 The symptoms of ATTS with the denervation in EDB are important to diagnose. In our case, CMAP of the peroneal nerve recorded at the right EDB muscle and motor unit potential and pathological spontaneous activity at right EDB muscle could not be obtained due to the atrophy of EDB.…”
mentioning
confidence: 99%
“…Furthermore, he established the electrodiagnostic technique to assist in the diagnosis. This syndrome occurs more commonly among women [4].…”
Section: Introductionmentioning
confidence: 99%
“…Within the tunnel are four tendons, an artery, a vein, and the deep peroneal nerve. DPN and its branches cross through this fibro-osseous canal by extending deep to the muscle tendons of the extensor hallucis longus and extensor digitorum longus towards the distal direction [3,4]. DPN innervates the peroneus tertius muscle and the dorsiflexors of the ankle and toes, including the tibialis anterior muscle, extensor digitorum longus and extensor hallucis longus, and extensor digitorum brevis (EDB) [5,6].…”
Section: Introductionmentioning
confidence: 99%